Nursing work in the surgical ward and psychosocial risks related to management modes - Bruna Pires Madrid; Kamille Kotekewis; Cecília Helena Glanzner
ABSTRACT Aim: To evaluate the management modes in the workplace of the nursing staff of the surgical ward of a university hospital. Methods: Cross-sectional, descriptive, quantitative and analytical study performed in the Surgical Ward of a university hospital in southern Brazil. Sample consisted of 160 nursing workers who answered the Management Styles Assessment Scale. Comparisons were made using Student's t-test and One-Way analysis of variance (ANOVA), Pearson's chi-square test, multiple comparisons test and multiple linear regression analyzes. Results: The Collectivist style was classified as "Predominant" by 46.2% (72) of the workers. The Normative and Directive styles were rated as "Moderate Presence" by 53.2% (84) and 50.3% (77), respectively. The Individualist style was rated as "Unremarkable" by 60.6% (94) of the sample. Conclusions: The presence of collectivist management meets the characteristics of nursing work, which is patient care, planned and performed jointly and in line with the multiprofessional team in the pursuit of comprehensive care.